A besta-fera vai ao paraíso: uma análise da construção da memória e identidade pública da médica e comunista maranhense Maria Aragão. - SILVA, Marcelo Fontenelle e (2017)
Maria Aragão was the center of a plenty of tributes and bibliografic references, particularly in the end of 1980s and after her death, in 1991, constituting herself as one of acknowledged character of Maranhão. Such productions were developed based on the great achievements of Maria, often mentioning her simultaneous condition as a physician, "communist leader" and a well regarted person. In an attempt of staying away of these usual stance among her biographers, the present research takes, as resources and object, parts of these tributes, biographic and autobiographic references, especially those ones produced between 1988 and 1992, with the aim of analyse the construction of the memory and public identity of this figure. It is also concerned in analyse how the dispute for the (re)construction of the past of the Maranhao State were unfolded, the process that alowed her to achieve such a prestigious position and parts of the dispute that she and her biographers envolved themselves before and during the production of such documents. Therefore, the present analyses brings up considerations about trajetory of Maria Aragão; agreements, disagreements and attempts of her own world view imposition to the space in which she was identified, always respecting the relational character of these definitions, that may vary depending on the position of each agent and how are developed the symbolic exchanges involving the attempts of appropriation of her "legacy".